Phenol‐enriched hydroxy depolymerized lignin by microwave alkali catalysis to prepare high‐adhesive biomass composites. Issue 5 (11th February 2021) - Di, Bing; Li, Zheng; Lei, Yin; Wang, Xiaofeng; Zhu, Yanchao; Qi, Wei; Tian, Yumei
Abstract: Lignin, a by‐product produced during pulping and papermaking, is a phenol‐rich compound with excellent prospect to be used as a substitute for phenol in phenolic resin adhesive. Phenol‐enriched hydroxy depolymerized lignin by microwave alkali catalysis is an effective method to prepare high‐adhesive biomass composite. This study investigated the microwave digestion of lignin under different conditions of the alkali catalysis (sodium hydroxide) concentration, power, reaction time, and reaction temperature. The results show that on the condition of sodium hydroxide concentration of 0.3 mol/L, temperature of 170 °C, and time of 20 min, the highest phenolic hydroxy content obtained by depolymerization of lignin is 21.68%. SEM shows that the depolymerized lignin has no original basic constituent units and lignin‐based phenolic resin has dense uniform pine needle units. Therefore, it has a high bonding strength of 1.934 MPa. The bonding strength and phenol content obtained by the microwave depolymerization method are much higher than those of other modification methods. Abstract :